Das Antworten verantworten Zur (Re-)Konzeptualisierung praktischer pädagogischer Reflexion anhand von Unterrichtsnachgesprächen im Kontext der zweiten Phase der Lehrer:innenbildung - Küper, Judith Elisabeth (Studien zur Professionsforschung und Lehrer:innenbildung, 2022)
Reflection is a key concept in the German discourse on teacher education. It is connected to the claim that professional educators should be able to adapt their actions according to situational demands and justify their decisions in ways that non-professionals could not. This ideal mirrors the refusal of a teacher education model which is based on the transmission of well-established practical routines. A high-quality reflection is associated with adopting an observer's point of view, permitting distance from the immediacy of pedagogical practice as well as access to scien- tific knowledge. Empirical studies on reflection situated in pedagogical practice instead suggest that adopting a distanced observer's point of view is not what pedagogical practitioners do when they reflect on their work. This discrepancy between the ideal and the practical phenomenon can either hint at a shortcoming of the examined practice - or it can draw attention to practical pedagogical reflection as a phenomenon in its own right. The latter could allow for a reading of practical pedagogical reflection beyond a deficit-oriented approach and highlight ethical dimensions of a mode of reflection that is not indifferent to its subject. This study is an attempt at reconceptualising practical pedagogical reflection as a phenomenon worth theorising. The aim of this venture is to develop a concept of reflection that is sensitive to pedagogical practice. The suggested reading intends to pluralise the dominant understanding of reflection and explore context-specific facets of the phenomenon in question.